2019
DOI: 10.1177/0142723719849996
|View full text |Cite
|
Sign up to set email alerts
|

Differences in sentence complexity in the text of children’s picture books and child-directed speech

Abstract: Reading picture books to pre-literate children is associated with improved language outcomes, but the causal pathways of this relationship are not well understood. The present analyses focus on several syntactic differences between the text of children’s picture books and typical child-directed speech, with the aim of understanding ways in which picture book text may systematically differ from typical child-directed speech. The analyses show that picture books contain more rare and complex sentence types, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 103 publications
5
46
0
Order By: Relevance
“…At the same time, teachers produced more diverse words when using wordless picture books in comparison to storybooks with text. By contrast, the mean length of teachers' utterances (sentences) was longer when using storybooks with texts compared to wordless picture books (Chaparro-Moreno et al, 2017), which is probably due to written sentences being longer and also more complex than spoken sentences in CDS (Cameron-Faulkner and Noble, 2013;Montag, 2019). Therefore, using wordless picture books instead of storybooks with text during dialogic reading is likely to be more effective in fostering vocabulary skills, but also likely to be less effective in fostering grammatical skills.…”
Section: Children's and Caregivers' Extratextual Talk During Shared Rmentioning
confidence: 98%
See 1 more Smart Citation
“…At the same time, teachers produced more diverse words when using wordless picture books in comparison to storybooks with text. By contrast, the mean length of teachers' utterances (sentences) was longer when using storybooks with texts compared to wordless picture books (Chaparro-Moreno et al, 2017), which is probably due to written sentences being longer and also more complex than spoken sentences in CDS (Cameron-Faulkner and Noble, 2013;Montag, 2019). Therefore, using wordless picture books instead of storybooks with text during dialogic reading is likely to be more effective in fostering vocabulary skills, but also likely to be less effective in fostering grammatical skills.…”
Section: Children's and Caregivers' Extratextual Talk During Shared Rmentioning
confidence: 98%
“…As a consequence, shared reading not only facilitates the basic learning of new words (vocabulary breadth), but also the acquisition of the words’ semantic features (vocabulary depth; Ouellette, 2006 ). On the sentence level, corpus analyses have shown that children’s books contain more complex grammatical constructions than CDS ( Cameron-Faulkner and Noble, 2013 ; Montag, 2019 ). Finally, on the text level, children’s books contain different narrative structures, providing a context in which children can learn to understand and (re-)produce narratives ( Pantaleo and Sipe, 2012 ; Wagner, 2013 , 2017 ).…”
Section: Shared Reading In the Hlementioning
confidence: 99%
“…Shared reading has been found to facilitate development across multiple domains (Doyle & Bramwell, 2006) in typically developing children (Teale & Sulzby, 1986) and those with language impairments (Gillam & Ukrainetz, 2006). Reading storybooks can be a powerful learning experience, frequently providing richer language models than are found in conversation (Montag, 2019). Moreover, interactive book reading has the ability to facilitate meaningful communication exchanges and the ability to expand children's language skills (Dickinson et al, 2012;Lovelace & Stewart, 2009) and is a commonly recommended practice (Kaderavek & Justice, 2002).…”
Section: Slps and Intentional Selection Of Diverse Booksmentioning
confidence: 99%
“…A key reason for the power of book reading in the first 3 years of life may be that book reading has been identified as the adult-child activity that generates more language input to the child than interactions during play or daily care-taking activities, such as feeding, bathing, and dressing (Dickinson & Morse, 2019;Hoff, 2003;Sosa, 2016). In addition, parents provide more sophisticated language models during story time than during other activities that include linguistic interaction: naturally occurring parent-child book interactions with 14-to 30-month-olds include greater parent vocabulary diversity and syntactic complexity than parent-child interactions that do not involve books (e.g., DeBaryshe, 1993;Demir-Lira et al, 2019;Montag, 2019). Book reading may therefore be an important language learning setting for preschool-aged children (e.g., Niklas et al, 2016).…”
Section: Why Promote Early Book Reading?mentioning
confidence: 99%